OBAT PENAWAR DAN PENYAKIT DI SAYAP LALAT (INTEGRASI-INTERKONEKTIF HADIS DENGAN ILMU PENGETAHUAN) - Muhammad Patri Arifin (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2020)
This article is a library research which aims to reveal the interconnectivity of hadith with science, with the hadith about flies as a case in point. At least, there are 4 patterns of relationship between religion and science, namely conflict, independence, dialogue, or integration. Without reflecting on these 4 patterns, the principle of understanding religion will not be possible to do perfectly, because it is separate from the reality of human life. By using thematic methods and historical-sociological approaches to these hadiths, this article arrives at the findings that most of the microorganisms such as germs, viruses and microbes that are present in the body of flies can cause a number of diseases, but the micro development of living things on the fluids they inhabit can neutralized by submerging it. This proves that the discovery of science is in harmony and synergy with the hadith of the Prophet.